Changing functional status within 6 months posttreatment is prognostic of overall survival in patients with head and neck cancer: NRG Oncology Study. Issue 11 (22nd August 2019) - Eldridge, Ronald C.; Pugh, Stephanie L.; Trotti, Andy; Hu, Kenneth; Spencer, Sharon; Yom, Sue S.; Rosenthal, David; Read, Nancy; Desai, Anand; Gore, Elizabeth; Shenouda, George; Mishra, Mark V.; et al.
Abstract: Background: Is posttreatment functional status prognostic of overall survival in patients with head and neck cancer (HNC). Methods: In an HNC clinical trial, 495 patients had two posttreatment functional assessments measuring diet, public eating, and speech within 6 months. Patients were grouped by impairment (highly, moderately, modestly, or not impaired) and determined if they improved, declined, or did not change from the first assessment to the second. Multivariable Cox models estimated overall mortality. Results: Across all three scales, the change in posttreatment patient function strongly predicted overall survival. In diet, patients who declined to highly impaired had three times the mortality of patients who were not impaired at both assessments (hazard ratio [HR] = 3.60; 95% confidence interval, 2.02‐6.42). For patients improving from highly impaired, mortality was statistically similar to patients with no impairment (HR = 1.38; 95% CI, 0.82‐2.31). Conclusions: Posttreatment functional status is a strong prognostic marker of survival in patients with HNC.